Land administration and regulation model for improved formal delivery and accessibility of urban lands in Nigeria. - Bolayemi, Akinbola Kazeem (2017)
Acquiring developable land for property development in suitable locations especially in urban areas is considered as a global problem, and is no exception in Nigeria. Some of the reasons responsible for this phenomenon are uncontrolled urbanisation, increasing demographic growth, complex bureaucracies, unskilled technocracy, corruption and weak institutional machineries, among others. All these had hampered smooth and efficient delivery processes and finally had decreased delivery and accessibility of urban lands in Nigeria. Therefore, this study was conducted, essentially to simplify the processes for land administrators while discharging their responsibilities, by examining and resolving those underlying factors that are affecting the optimal performance of formal land administration and regulation systems. This study adopted quantitative approach, with the use of both probabilistic and non-probabilistic sampling techniques. The respondents participated in this study were relevant government agencies and committees that are directly involved in the supply of urban land; low, medium and high density land users in eighteen (18) formal land development schemes, from two cities in each of six states of the Southwestern Nigeria. These schemes were found in Isheri and Ikorodu in Lagos State; Abeokuta and Ijebu-Ode in Ogun State; Ibadan and Ogbomoso in Oyo State; Osogbo and Ile-Ife in Osun State; Akure and Ondo in Ondo State; and Ado-Ekiti and Ijero-Ekiti in Ekiti State. Furthermore, the independent land consultants and shelter or land mandated non-governmental organisations (NGOs) were considered as the intermediate component of the land delivery and accessibility equation; so as to have balanced results that are sufficient to address these challenges. By using the Analysis of Moments of Structures Software Package (AMOS), via Structural Equation Modelling (SEM), the results show that merely nine percent (9%) of causal relationship exists between the duo of formal land administration and regulation system (FLARS) and policy development and compliance engineering (PDCE), as determining agents of formal land delivery and accessibility in Nigeria. Furthermore, these are due to the stand-alone structure of the lands regulo-administrative machineries, leading to their insignificant contribution of nine percent (9%) towards formal land delivery and accessibility. As a conclusion, close to 70% of these challenges were caused by ill-structuration, corruption, lack of collaboration and policy summersault, and thus will remain unsolved if this trend continues. Among the suggestions is that, there should be improvement to land administration operations which can be achieved through SLADECOM Model applications, where restructuring of departments and land administration regulation systems, as well as policy frameworks will be made to improve the efficiency and performances of land administration and regulation systems in Nigeria.